Mencari Makna Dalam Sejarah: Meninjau Kembali Historiografi Indonesiasentris Sebagai Sumber Belajar Sejarah - Kurniawati Kurniawati (Jurnal Pendidikan Sejarah, 2015)
This article describes the historiography toward Indonesia after independence and its relevance to the teaching of history at the time.The Method used in writing this article is the research literature. Writing the history of Indonesia, which has a style Indonesiacentric is an issue that has always promoted in the historiography Indonesia. Since independence in 1945, a form of history writing seeks embodied Indonesiacentric.Therefore it seeks a National History Congress was held to formulate the form of historiography Indonesiasentric but Congress was not fully able to formulate clearly .Historiografi Indonesia finally caught up to the political interests that lead to the deconstruction of old regime history. History teacher thus becomes very important in answering the anxiety people especially students in learning history.Curriculum 2013 gives greater space to the history teachers to design learning history allows students not only rely on textbooks but explores a variety of sources and historiography are available.